Further chronicles of avonlea ebook - Montgomery, L. M. (Lucy Maud) (Chronicles of Avonlea, 2012)
Travel to the tranquil seaside village of Avonlea in this charming collection of tales from acclaimed author L. M. Montgomery. From lighthearted stories about pampered pets and love triangles to more serious accounts of tragic loss, this varied volume is sure to please readers who fell in love with Chronicles of Avonlea or Montgomery's masterpiece, Anne of Green Gables .